Production of glycosphingolipids intermediates by fermentation at laboratory scale - Carvalho, Ana Cristina Gouveia (2023)
Sphingolipids, a class of lipids which comprise a sphingoid base in their backbone are present in the cell membrane, helping in the formation, maintenance and the regulation of cellular processes, such as cell growth and apoptosis. Sphingolipids can be obtained through chemical synthesis or biotechnological route, with the latter being more environmentally friendly, cost-effective and promising for large-scale production. Phytosphingosine, when produced through fermentation with Wickerhamomyces ciferrii, comes in its acetylated form with tetraacetylphytosphingosine being the most common form. CarboCode aims to produce phytosphingosine, through aerobic fed-batch fermentation with W. ciferrii for health, skin care and nutrition applications. The goal of this internship was to contribute to the optimization of the bioprocess currently employed by replacing the use of pure glycerol with crude glycerol (CG), a cheaper carbon source, in the fermentation medium. In addition, this work also aimed to provide insights into the scale-up process of this bioprocess by performing oxygen transfer and uptake studies in a standard CarboCode fermentation. To accomplish the first objective, increasing percentages of CG from Fábrica Torrejana, namely 25, 50, 75 and 100%, were combined with pure glycerol in batch shake flask assays and, the percentages of 50, 75 and 100% CG in the fermentation medium and feed solution in fed-batch bioreactor assays. In the bioreactor, volumetric mass transfer coefficient (kLa) was measured under different airflows and stirring conditions in distilled water through the dynamic desorption-absorption method. Oxygen uptake rate (OUR), specific oxygen uptake rate (q O₂) and kLa were assessed in a standard fermentation with respirometry assays. Results from shake flask assays showed that the impurities present in the CG affected the yeast growth, but clear patterns regarding phytosphingosine production were not observed. From the percentages tested, 100 % CG, showed the highest concentration of A (xx ± xx mg Lˉ¹) while the fermentations with 75 % CG provided the highest concentration of B (yy ± yy mg Lˉ¹). During bioreactor assays, fermentation with 50 % CG showed the best results, with final titers of xx g Lˉ¹ of B and yy g Lˉ¹ of A, allowing a zz % decrease of costs related to the carbon source. Through the dynamic desorption-absorption method, the highest kLa obtained was xx hˉ¹ with an airflow of yy L minˉ¹ and zz rpm. During respirometry assays, both maximum q O₂ and OUR were achieved in the batch and beginning of fed-batch, xx mmol O₂ gˉ¹ hˉ¹ and yy mmol O₂ Lˉ¹ hˉ¹, respectively.